Lactate-enhanced production of a cyclic β-1,2-glucan in Acetobacter pasteurianus - Yong Chen; Yihang Qi; Zhongya Zhou; Xin Liu; Yaping Sun; Ting Liu; Mengru Wu; Hui Li; Jing-yi Zhao; Zijun Xiao (Food Microbiology, 2027)

Beyond correlation: Time-resolved conditional-effect mapping of component-coupled NOX, SO2, and HCl release and multipollutant risk shifts during industrial organic solid waste incineration - Yaping Qi; Fansong Meng (Journal of Environmental Chemical Engineering, 2026)

Decoding hydrometallurgical kinetics of spent lithium-ion batteries via time-series generative adversarial network-driven data augmentation and machine learning to address data scarcity - Yaping Qi; Fansong Meng (Journal of Environmental Chemical Engineering, 2026)

Next-generation intelligent prepared aquatic dishes: research progress in digital heat control and quality evaluation empowered by industry 4.0 - Ying Xie; Min Zhang; Qi Yu; Yaping Liu (Food Research International, 2026)

Characterization of T5DL·5DS-2RS, a wheat-rye chromosomal translocation with enhanced grain hardness and pre-harvest sprouting resistance - Xin Liu; Huiting Zhang; Zhenglan Cao; Yanhong Lei; Mengyu Han; LiBin Wang; Yilong Dong; Jishan Niu; Yaping Cao; Jiajia Zhao; Jun Zheng; Xueming Yang; et al. (Theoretical and Applied Genetics, 2026)

Characterisation of ginsenosides composition in processed American ginseng products using UPLC-MS coupled with chemometric analysis - Chang Wang; Xiaolei Tang; Haiyu Chen; Yaping Wang; Xitong Yuan; Daqing Zhao; Baotai Huang; Li Liu; Bin Qi (Natural Product Research, 2026)

Non-sampling estimation of waste composition based on incineration flue gas pollutant fingerprints and machine learning approach - Yaping Qi; Pinjing He; Fan Lü; Hua Zhang (Journal of Environmental Sciences, 2026)

Based on sensory evaluation, E-nose, and GC-IMS analysis of volatile component differences in various kinds of sheep fats - Yaping Wang; Xiaolei Tang; Xitong Yuan; Hanying Xu; Yuxi Liu; Yaling Yang; Zhihui Lin; Siming Wang; Bin Qi; Li Liu (Natural Product Research, 2026)

Effects of thermal alkaline hydrolysis and biochar addition on anaerobic digestion of sewage sludge and fate of antibiotic resistance genes - Ruoxin Li; Chunsheng Qiu; Xu Chen; Nannan Liu; Yaping Zhang; Li Qi; Shaopo Wang (Bioresource Technology, 2026)

Quantitative and qualitative comparison of grain-size parameters in different types of sediments using graphic and moment methods - Yuehua Qi; Mingliang Li; Gaocong Li; Jieping Tang; Lintao Zhao; Yaping Wang; Mingming Yuan (Acta Oceanologica Sinica, 2026)

Profiling 32 alkaloid compounds from Macleaya cordata by UPLC-DAD–QTOF-MS/ms - Xinji Zhou; Yuqing Peng; Hao Zhou; Wenyan Wang; Gui Yi; Qi Xia; Yaping Guo; Lianwu Xie (Natural Product Research, 2026)

Effect of PEDV infection on IPEC-J2 cells on miR-328–3p/FoxO4/NF-κB/MLCK signaling axis - Yiming Wei; Zixuan Qi; Yaping Shuai; Shihui Zhao; An Liu; Jiuyuan Liu; Di Bao; Han Zhao; Shuang Zhang; Hongze Shao; Shushuai Yi; Jiangting Niu; et al. (Veterinary Microbiology, 2025)

Highly efficient biophotoelectrochemical methanogenesis coupling with water sterilization via robust interfacial electronic communication - Jing Hu; Chaohui Yang; Yaping Qi; Mingqiu Hong; Jiajing Chen; Guoping Ren; Jie Ye (Chemical Engineering Journal, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Assessing Fluoride Contamination in Groundwater of Informal Landfills in the Yangtze River Delta: Implications for Environmental Security and Sustainable Resource Management - Lichen Liang; Xiaofei Yan; Yaping Qi; Lili Wang; Haifeng Tu; Hao Jiang; Dan Wang; Houhu Zhang; Yuanshun Xu (Water, Air, & Soil Pollution, 2025)

Vegetation and climate dynamics in Southwestern China during the Han and Jin Dynasties (202 BC-AD 420): Insights from the Spore-pollen and hydrological records from the Chengba site - Junna Zhang; Liu Qi; Yaping Li; Weidong Chen; Luhong Zheng; Xueran Wang; Songhan Li; Bingyuan Zhang (Quaternary International, 2025)

CmERFIV-4-CmWRKY44-CmPSY1 modulates ethylene-induced β-carotene accumulation in oriental melon fruit - Fei Luo; Xiaoyu Duan; Ge Gao; Yaping Zhao; Meng Li; Hongyan Qi (Postharvest Biology and Technology, 2025)

Combinatorial metabolic engineering of Escherichia coli to efficiently produce L-threonine from untreated cane molasses - Xin Jin; Sumeng Wang; Yaping Gao; Qingsheng Qi; Quanfeng Liang (Bioresource Technology, 2025)

A new evolutionary topology optimization method for truss structures towards practical design applications - Yaping Lai; Qi Cai; Yu Li; Jiayong Chen; Yi Min Xie (Engineering Structures, 2025)

Combined biochar and wheat-derived endophytic bacteria reduces cadmium uptake in wheat grains in a metal-polluted soil - Zhihui Xiong; Yaping Wang; Linyan He; Qi Sheng; Xiafang Sheng (Journal of Environmental Sciences, 2025)

Multi-omics analysis reveals anthocyanin synthesis is associated with drought stress tolerance in Chaenomeles speciosa flowers - Shuangyu Zhang; Xiling Chen; Yanshen Ren; Xingyue Xue; Yaping Xu; Qi Wang; Yanru Xie; Tengxun Zhang; Jiayi Lin; Xiaolu Chen; Houhua Li (Journal of Cleaner Production, 2024)

Status and trends of artificial intelligence in the R & D of future fruit & vegetable juice - Huanhuan Niu; Min Zhang; Qi Yu; Yaping Liu (Innovative Food Science & Emerging Technologies, 2024)

Enhanced reductive catalytic fractionation of lignocellulose using a water-resistant RuNiZnOx/Nb2O5 catalyst with synergistic hydrogen spillover and acidic properties - Zhaozhuo Yu; Wenzhuo Kong; Yaping Guo; Wen Liang; Jiawei Liang; Meijuan Chen; Dongxu Zhao; Hongzhen Ma; Xiangjun Liu; Solomon Inalegwu Okopi; Lei Che; Qi Zhang; et al. (Fuel, 2024)

Machine learning framework develops neutrophil extracellular traps model for clinical outcome and immunotherapy response in lung adenocarcinoma - A. Xuan Han; B. Yaping Long; C. Yao Li; D. Di Huang; E. Qi Xiong; F. Jinfeng Li; G. Liangliang Wu; Qiaowei Liu; G. Bo Yang; H. Yi Hu (Apoptosis, 2024)

Identification of nsLTP family in Chinese white pear (Pyrus bretschneideri) reveals its potential roles in russet skin formation - Jiawei Li; Qi Wang; Yajing Wang; Xinyi Wu; Yaping Liu; Minchen Wan; Lindu Wang; Xiexuan Wang; Cheng Zhang; Xueqian Wang; Xiaomei Tang; Wei Heng (Planta, 2023)

Gastrodin ameliorates exercise-induced fatigue via modulating Nrf2 pathway and inhibiting inflammation in mice - Yaping Zhou; Qi Wu; Wen Yu; Fan Ye; Yunyun Cao; Otobong D. Akan; Xiuxiu Wu; Tiantian Xie; Han Lu; Fuliang Cao; Feijun Luo; Qinlu Lin (Food Bioscience, 2023)

Assessment of Fungal Diversity in Minqin County, a Typical Arid Region in Northwestern China - Zhanwu Peng; Shuwei Wei; Yaping Hu; Bao Qi; Chaofeng Yuan; Qi Wang; Yu Li (Current Microbiology, 2023)

Higher pH is associated with enhanced co‐occurrence network complexity, stability and nutrient cycling functions in the rice rhizosphere microbiome - Yaping Guo; Bin Song; Anqi Li; Qi Wu; Haili Huang; Na Li; Ying Yang; Jonathan Miles Adams; Lin Yang (Environmental Microbiology, 2022)
The rice rhizosphere microbiota is crucial for crop yields and nutrient use efficiency. However, little is known about how co‐occurrence patterns, keystone taxa and functional gene assemblages relate to soil pH in the rice rhizosphere soils. Using shotgun metagenome analysis, the rice rhizosphere microbiome was investigated across 28 rice fields in east‐central China. At higher pH sites, the taxonomic co‐occurrence network of rhizosphere soils was more complex and compact, as defined by higher average degree, graph density and complexity. Network stability was greatest at medium pH (6.5

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Conversion of organics and minerals into electricity and microalgae using a dual-membrane cylinder photo-microbial fuel cell - Gang Li; Haixing Chang; Yajun Zou; Jianzhi Yue; Yaping Zheng; Haowen Feng; Haihua Wu; Wenbo Wu; Jie Lou; Xueqiang Qi; Xingran Zhang (Environmental Chemistry Letters, 2021)

Trueperella pyogenes pyolysin inhibits lipopolysaccharide-induced inflammatory response in endometrium stromal cells via autophagy- and ATF6-dependent mechanism - Maozhen Qi; Jianguo Liu; Qingran Jiang; Hongyu Niu; Xinyu Wang; Dong Zhou; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin (Brazilian Journal of Microbiology, 2021)

A Fluorescent “Turn-off” Probe for the Determination of Curcumin Using Upconvert Luminescent Carbon Dots - Chenhong Yu; Qi Zhuang; Hanyue Cui; Li Li; Yaping Ding; Jiaxin Lin; Yingchun Duan (Journal of Fluorescence, 2020)

Effect of ionic liquid [MIm]HSO4 on WPCB metal-enriched scraps refined by slurry electrolysis - Yaping Qi; Xiaoxia Yi; Yugai Zhang; Fansong Meng; Jiancheng Shu; Furong Xiu; Zhi Sun; Shuhui Sun; Mengjun Chen (Environmental Science and Pollution Research, 2019)

Probiotics decrease depressive behaviors induced by constipation via activating the AKT signaling pathway - Nana Xu; Wenting Fan; Xiaoyan Zhou; Yaping Liu; Ping Ma; Suhua Qi; Bing Gu (Metabolic Brain Disease, 2018)

Molecular mechanism of elicitor-induced tanshinone accumulation in Salvia miltiorrhiza hairy root cultures - Guoyin Kai; Pan Liao; Hui Xu; Jing Wang; Congcong Zhou; Wei Zhou; Yaping Qi; Jianbo Xiao; Yuliang Wang; Lin Zhang (Acta Physiologiae Plantarum, 2012)

The Polymorphism of DNA Repair Gene ERCC2/XPD Arg156Arg and Susceptibility to Breast Cancer in a Chinese Population - Jiaoyang Yin; Duohong Liang; Ulla Vogel; Yaping Chang; Zhengrong Liu; Li Yue; Xiaoling Sun; Rong Qi; Tiehua Song (Biochemical Genetics, 2009)